Unilateral subcondylar fracture treated by close reduction: A case report - AE Noor; N Amin; TG Chowdhury; Md Mahfuz Hossain; Shahed Jahan; Asma Sultana (Update Dental College, 2015)
This case report is an insight in to Oral and Maxillofacial Surgery whereby close reduction to unilateral condylar fracture is used as a means to highlighting the fact that dental surgeons require a unique understanding of the anatomy, growth considerations, healing pattern and operative management involving minimal manipulation while managing unilateral condylar fractures. Update Dent. Coll. j: 2014; 4 (2): 20-22